A deep learning algorithm for sleep stage scoring in mice based on a multimodal network with fine-tuning technique. (December 2021) - Akada, Keishi; Yagi, Takuya; Miura, Yuji; Beuckmann, Carsten T.; Koyama, Noriyuki; Aoshima, Ken
Highlights: The new proposal of the sleep stage classification algorithm. It was developed with a new deep neural network algorithm. It provides adequate performance for wake, REM sleep, and NREM sleep. The multimodal with fine-tuning approach showed high potential. Abstract: Sleep stage scoring is important to determine sleep structure in preclinical and clinical research. The aim of this study was to develop an automatic sleep stage classification system for mice with a new deep neural network algorithm. For the purpose of base feature extraction, wake-sleep and rapid eye movement (REM) and non- rapid eye movement (NREM) models were developed by extracting defining features from mouse-derived electromyogram (EMG) and electroencephalogram (EEG) signals, respectively. The wake-sleep model and REM-NREM sleep model were integrated into three different algorithms including a rule-based integration approach, an ensemble stacking approach, and a multimodal with fine-tuning approach. The deep learning algorithm assessing sleep stages in animal experiments by the multimodal with fine-tuning approach showed high potential for increasing accuracy in sleep stage scoring in mice and promoting sleep research.